Code underlying publication: "Regional dissection of subpolar North Atlantic overturning reveals complex spatial heterogeneity indicative of governing processes" ... - Vermeulen, Dennis; Gelderloos, Renske; Katsman, Caroline (4TU.ResearchData, 2025)
Collection of analysis routines and plotting helpers that accompany the manuscript "Regional dissection of subpolar North Atlantic overturning reveals complex spatial heterogeneity indicative of governing processes", submitted to Journal of Physical Oceanography in 2025. All functions are implemented using xarray, numpy, scipy and matplotlib. The file can be executed as a script to reproduce all figures included in the manuscript. All modules necessary to run are mentioned in the first section of the code. Any units follow the SI convention unless otherwise noted. ...